An economically viable synthesis of biodiesel from a crude Millettia pinnata oil of Jharkhand, India as feedstock and crab shell derived catalyst. (August 2016) - Madhu, Devarapaga; Chavan, Supriya B.; Singh, Veena; Singh, Bhaskar; Sharma, Yogesh C.
Graphical abstract: Highlights: Crude commonly found in Jharkhand used as a feedstock. A heterogeneous catalyst derived from crab shell used for transesterification. High yield of biodiesel obtained. Catalyst usable up to 5 times without loss of activity. Entire process is economically viable. Abstract: Biodiesel has emerged as a prominent source to replace petroleum diesel. The cost incurred in the production of biodiesel is higher than that for refining of crude oil to obtain mineral diesel. The heterogeneous catalyst was prepared from crab shells by calcining the crushed mass at 800 °C. The solid waste catalyst was characterized with XRD, XPS, BET, SEM–EDS, and FT-IR. Millettia pinnata (karanja) oil extracted from its seeds was used as a feedstock for the synthesis of biodiesel. Biodiesel was synthesized through esterification followed by transesterification in a two-step process. Characterization of biodiesel was done using proton NMR spectroscopy. Reaction parameters such as reaction time, reaction temperature, concentration of catalyst and stirrer speed were optimized. Reusability of catalyst was checked and found that there was no loss of catalytic activity up to five times.